Accommodation Needs for Teachers Who are Blind and Teach Students with Visual Impairments. (May 2019) - Okungu, Phoebe A.; Griffin-Shirley, Nora; Pogrund, Rona L.
Introduction: This study was intended to explore and identify the experiences and perceptions of teachers of students with visual impairments who are blind concerning their accommodation needs and to establish their opinions on what improvements can be made. Method: A qualitative case study design was used and was collected through interviews, observations, and documents. Participants were four teachers who are blind who taught students with visual impairments in mainstream public and specialized residential schools in the United States. Within-case and cross-case levels of data analysis were used to generate and compare the themes that emerged. Results: The results illuminated accommodation issues for the teachers in the areas of family support, strategies the teachers use, challenges in their workplaces, and suggestions regarding possible improvements. Discussion: This study generated answers to the pertinent research questions. The study has revealed that the participants use different types and forms of accommodations to accomplish tasks. Some accommodations used include computer technology, assistive devices, and sighted assistants. However, the participants expressed that access to these accommodations are not consistent for all individuals who are blind. The participants also identified the accommodation challenges that are related to their blindness and provided suggestions for possible improvements. Implications for practitioners: Teachers of students with visual impairments who are blind need to be self-advocates in their personnel preparation programs and in their workplaces concerning the accommodations they need to accomplish job tasks.